PENGARUH APLIKASI DAPODIK TERHADAP MOTIVASI KINERJA PENDIDIK PAUD DAN KEBIJAKAN PADA PAUD DI KABUPATEN NGANJUK - DEDY TJAHJONO (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
The Dapodik application is a computer application carried out by the Ministry of Education and Culture of the Republic of Indonesia so that schools or educational units can report basic education data directly to online services via the internet network without the need to be limited by distance and time problems. One of the related data is PAUD educators/teachers who are required to be professional, responsible for planning, implementing and assessing learning outcomes, as well as providing guidance, care and protection for students/students. This should be the motivation for the highest performance in early childhood education with policy support at the organization or institution. The purpose of this study was to determine the effect of Dapodik application on early childhood educator performance motivation, Dapodik application effect on Early Childhood Education policy and the extent to which Dapodik application affects early childhood education performance motivation and early childhood policy in Nganjuk Regency. This research is a type of field research using a sampling method of 100 people. The method of data collection is done by using a questionnaire, where the variables are measured using a Likert scale. This research approach is quantitative by describing a problem using analysis in the form of numbers or numbers. Furthermore, data processing using SPSS version 2.5 software. While the use of multiple linear analysis to determine how much influence the independent variable has on the dependent variable and the use of simple linear regression s to measure the influence of the independent variable on the dependent variable and predict the dependent variable using the independent variable. The results showed that: (1) partially there was a significant positive relationship on the effect of the Dapodik Application variable on the Motivation for Early Childhood Educator Performance in Nganjuk Regency; (2) partially there is a significant positive relationship on the effect of the Dapodik Application variable on the Policy variable at PAUD in Nganjuk Regency; (3) Through the results of the data from the cross-tabulation test, there is an increase in the performance motivation of PAUD educators and policies in PAUD from the effect of dapodik applications in this study of 69.30% stating